DOSIMETRY WITH SALT IN MIXED RADIATION FIELDS OF PHOTONS AND NEUTRONS. Issue 3 (22nd August 2017) - Ekendahl, Daniela; Rubovič, Peter; Žlebčík, Pavel; Huml, Ondřej; Malá, Helena
Abstract: Salt (NaCl) represents a radiation sensitive material with a considerable potential for dosimetry in mixed radiation fields of photons and neutrons. In consequence of a gamma radiation exposure, it exhibits a strong luminescence signal following stimulation with blue light. Optically stimulated luminescence (OSL) technique can be used for measurement. Photon dose reconstruction can be done using so-called Single-Aliquot Regenerative-dose protocol. However, a part of OSL signal is caused by NaCl self-irradiation resulting from neutron reactions. This NaCl neutron sensitivity is comparable with neutron sensitivity of TLD-700. Neutron dose can be determined based on neutron activation of NaCl via reaction 23 Na(n, γ) 24 Na. A relation between neutron dose and activity of 24 Na can be derived. The total dose is thus determined based on the combination of results of OSL measurements and gamma activity measurements. Practical feasibility of this approach was experimentally verified for salt samples irradiated in a channel of a training reactor.